Performance of IBS lightweight cold-formed steel roof truss - Al-Shaquerin, Katman (2012)
Cold-formed steel has been recently brought into Malaysian construction. It is a steelwork technology that has high potential to be developed in Malaysia, that can offers advantages such as fast erection, lightweight, clean and easier construction. This paper reported a series of research studies carried out in UMP for locally produced cold formed steel sections. The research work included study on the member capacities for lipped C-section and Hat-section, a test for roof truss system member. The objective of this study, which base from the code is practice to analyze several C-cross-section and hat section of steel design from cold formed from different material (Zincalume, Galvanized and Truecore) for its strength to sustain axial load. The interest capacities are compression strength, moment capacity and yield strength. All the studies were based on the requirements of British Standard BS 5950 Part 5 1998. The results of the experimental tests on the proposed cold-formed steel section and roof truss system showed good agreement to the requirements of BS5950 Part 5 1998.